Sleeping In Sitting Posture Analysis Of Economy Class Aircraft Passenger - Tan, Chee Fai; Chen, Wei; Kimman, Floris; Rauterberg, Matthias (Springer Netherlands, 2010)
With the rapid development of technology, the comfort of service has become an important issue. Air travels, especially long distance, may cause both physiological and psychological discomfort to passenger. Passenger comfort is clearly a main factor in user’s acceptance of transportation systems. Sleeping is one of the common activities during the long haul flight. In this paper, subjective and objective measurement method was described to evaluate the sleeping in sitting posture of economy class aircraft seat passenger.